Direct ophthalmoscopy on YouTube: analysis of instructional YouTube videos’ content and approach to visualization - Borgersen, Nanna Jo (Clin Ophthalmol, 2016)
BACKGROUND: Direct ophthalmoscopy is well-suited for video-based instruction, particularly if the videos enable the student to see what the examiner sees when performing direct ophthalmoscopy. We evaluated the pedagogical effectiveness of instructional YouTube videos on direct ophthalmoscopy by evaluating their content and approach to visualization. METHODS: In order to synthesize main themes and points for direct ophthalmoscopy, we formed a broad panel consisting of a medical student, junior and senior physicians, and took into consideration book chapters targeting medical students and physicians in general. We then systematically searched YouTube. Two authors reviewed eligible videos to assess eligibility and extract data on video statistics, content, and approach to visualization. Correlations between video statistics and contents were investigated using two-tailed Spearman’s correlation. RESULTS: We screened 7,640 videos, of which 27 were found eligible for this study. Overall, a median of 12 out of 18 points (interquartile range: 8–14 key points) were covered; no videos covered all of the 18 points assessed. We found the most difficulties in the approach to visualization of how to approach the patient and how to examine the fundus. Time spent on fundus examination correlated with the number of views per week (Spearman’s ρ=0.53; P=0.029). CONCLUSION: Videos may help overcome the pedagogical issues in teaching direct ophthalmoscopy; however, the few available videos on YouTube fail to address this particular issue adequately. There is a need for high-quality videos that include relevant points, provide realistic visualization of the examiner’s view, and give particular emphasis on fundus examination.